Precise orbit determination of Beidou Satellites with precise positioning - Shi, Chuang; Zhao, QiLe; Li, Min; Tang, WeiMing; Hu, ZhiGang; Lou, YiDong; Zhang, HongPing; Niu, XiaoJi; Liu, JingNan (Science China. Earth sciences, 2012)
Chinese Beidou satellite navigation system constellation currently consists of eight Beidou satellites and can provide prelimi- nary service of navigation and positioning in the Asia-Pacific Region. Based on the self-developed software Position And Navigation Data Analysis（PANDA） and Beidou Experimental Tracking Stations （BETS）, which are built by Wuhan University, the study of Beidou precise orbit determination, static precise point positioning （PPP）, and high precision relative positioning, and differential positioning are carried out comprehensively. Results show that the radial precision of the Beidou satellite orbit determination is better than 10 centimeters. The RMS of static PPP can reach several centimeters to even millimeters for base- line relative positioning. The precision of kinematic pseudo-range differential positioning and RTK mode positioning are 2-4 m and 5-10 cm respectively, which are close to the level of GPS precise positioning. Research in this paper verifies that, with support of ground reference station network, Beidou satellite navigation system can provide precise positioning from several decimeters to meters in the wide area and several centimeters in the regional area. These promising results would be helpful for the implementation and applications of Beidou satellite navigation system.